دور مهارات الإتصال التربوي لدى لأساتذ التربية البدنية والرياضية في تحقيق أهداف الحصة في مرحلة التعليم المتوسط - ثابتي, محمد (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
عنوان البحث: "دوراستخدام مهارات الإتصال التربوي لأستاذ التربية البدنية والرياضية في تحقيق أهداف الحصة في مرحلة التعليم المتوسط" تهدف الدراسة التي بين أيديكم إلى معرفة مساهمة مهارات الإتصال التربوي لأستاذ التربية البدنية والرياضية في تحقيق الأهداف المعرفية الإدراكية والأهداف الحسية الحركية للتلاميذ في المرحلة المتوسطة. ولأجل ذلك اتبعنا المنهج الوصفي المسحي بالإعتماد على استبيان للأساتذة وآخر موجه للتلاميذ، حيث تمثلت عينة الأساتذة في 12 أستاذ وعينة التلاميذ في 60 تلميذ وتلميذة من مرحلة التعليم المتوسط، اختيروا بطريقة قصدية. وجاءت أهم نتائج البحث بأن لمهارات الإتصال التربوي لأستاذ التربية البدنية والرياضية تأثير ايجابي على تحقيق أهداف الحصة في مرحلة التعليم المتوسط. // // // // Research Summary Research Title: "The Role of Educational Communication Skills of Physical Education Teachers in Achieving Lesson Objectives in the Middle School Stage" This study aims to investigate the contribution of the educational communication skills of physical education teachers in achieving cognitive, perceptual, and motor skill objectives among students in the middle school stage. The research adopted a descriptive survey method, utilizing questionnaires administered to teachers and students. The teacher sample comprised 12 physical education teachers, while the student sample included 60 students from the middle school stage, selected purposively. The key findings of the research indicate that the educational communication skills of physical education teachers have a positive impact on achieving lesson objectives in the middle school stage.
MES-2024-21
Keywords: مهارات الاتصال - أستاذ التربية البدنية - المرحلة المتوسطة // // // Communication Skills - Physical Education Teacher Middle School